ANALISIS EFEKTIVITAS IMPLEMENTASI KEBIJAKAN SENSUS PAJAK NASIONAL PADA DIREKTORAT JENDERAL PAJAK SURABAYA - Ferianto, Ahmad; titik (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
The purpose of this research is to analyze the effectiveness and the implementation of National Tax Census policy in the environment of Regional Office of Directorate General of Taxation East Java I Surabaya. Qualitative approach with the descriptive analysis is used in this research. The data collection is carried out by using literature study, statistics data, documentation and interview with the correspondent. The analysis of effectiveness is adopted from Value for Money based public sector performance assessment whereas the policy of implementation is focused on the mechanisms and the problems in the technical implementation of National Tax Census.The result of the analysis shows that (1) the implementation of National Tax Census policy has been reached properly; there are some indicators of success i.e.: disposition, communication, the structure of bureaucracy and its resources. (2) Yet, there is still an obstacle in the policy implementation such as: the difficult customers to make meeting appointment, public resistance (3) the implementation of national tax census in 2011 is in less effective category with the effectiveness ratio is 68.74 %. However, the implementation of national tax census in 2012 experienced improvement with its effectiveness ratio is 82.19 % that is in quite effective category.